(untitled) (Washington, 2002)
The book begins by establishing baseline information on the tourism industry, situating ecotourism within the larger tourism industry, and tracing the history of certification. The second chapter explores the concepts underlying certification followed by a chapter that examines certification as a tool in other industries such as forestry and coffee production. The remainder of the book highlights case studies of the most promising certification schemes around the world. Written by experts who have been closely involved with the projects described, case studies include: the NEAP Program in Australia, Costa Rica's government-financed Sustainable Tourism Certification (CST) program and other programs in Central America, more than 50 eco-labeling and certification programs for accommodations in Europe, programs to certify beaches and national parks, efforts in South Africa and Kenya to establish certification programs
Keywords: Ecotourism,Eco-labeling; Certification